Indigenous forestry - Mapedza, Everisto D. (2010)
Indigenous forestry started getting recognition after the failure of state-dominated forestry, which excluded historical forestry management by indigenous and local communities. Indigenous forestry is defined as an approach that sees local indigenous forestry users as taking a central role in how their resources are managed and used. The indigenous forestry approach contrasts with conventional or scientific forestry, which brings in outside knowledge that indigenous people are then forced to use in planning, management, and use of their forests.